Social media e pandemia. Il Movimento inconsapevole - Gozzo, Simona; D'Agata, Rosario; Giuffrida, Giovanni (SocietàMutamentoPolitica, 2023)
The massive diffusion of social media has produced disintermediation and it has changed the way in which users inform themselves and participate in public debate. On the other hand, users show a tendency to interact with information that adheres to personal choices and previous opinions. This propensity is “exploited” by algorithms that manage and sort communication on social media, increasingly producing a polarized audience. The essay shows the outcomes of these dynamics by focusing on the communications structure related to the pandemic. In this sense, social media constitute a risk because they convey out-of-control access to unreliable information and because they can result in the absence of correct information, if not in a problem for democracy. On the technical level, at least three complex reticular structures are identified that evolve following different directions, emerged from three sequentially monitored lemmas (no-mask, covid-19, greenpass). Further considerations concern the increasingly dense interweaving between online communication and the genesis of protest movements with evanescent, single-issue structures.